THE INFLUENCE OF AFFECTIVE FACTORS ON LISTENING COMPREHENSION: ANXIETY AND DISTRACTION IN EFL CONTEXTS - qizi, Oxunova Nargiza Xayrullo; qizi, Scientific adviser: Abdusattorova Muxarram Sharifjon (Research Focus International Scientific Journal, 2026)
This study investigates the effects of anxiety and distraction on students’ listening comprehension in an EFL context. The data were collected through questionnaires observations, and interviews with third-year students. The results show that most students experience nervousness and lose concentration during listening tasks, which negatively affects their performance. To solve this problem, the “Double Listening with Focus” method was applied and it helped students become more confident and focused and improved their listening comprehension.